2021
DOI: 10.7759/cureus.12440
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Complications Among Pediatric Patients With Sickle Cell Anemia: A Single Tertiary Center Retrospective Study

Abstract: Background and objective Sickle cell anemia (SCA) is one of the common genetic diseases in the Kingdom of Saudi Arabia (KSA). This disease results from a genetic mutation that causes malformation of the red blood cells (RBCs), leading to various systemic complications, including vaso-occlusive crisis (VOC), acute chest syndrome (ACS), osteomyelitis, avascular necrosis (AVN), and stroke, to name a few. The leading cause of mortality in SCA is these systemic complications rather than the disease itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…In Kuwait, the prevalence of stroke is 1.4% in children [30], and in Shiraz, Iran, it seems to be low among children with SCD. When adults are considered, the stroke prevalence is high in Saudi Arabia's provinces (~7%) [31][32][33][34].…”
Section: Prevalence Of All Strokes In People With Scd Who Do Not Get ...mentioning
confidence: 99%
“…In Kuwait, the prevalence of stroke is 1.4% in children [30], and in Shiraz, Iran, it seems to be low among children with SCD. When adults are considered, the stroke prevalence is high in Saudi Arabia's provinces (~7%) [31][32][33][34].…”
Section: Prevalence Of All Strokes In People With Scd Who Do Not Get ...mentioning
confidence: 99%
“…One paediatric study from high and low altitude regions of SouthWest Saudi Arabia reported 8/400 (2%) over a 3 year period [ 51 ] but 9/90 (10%) of a series of children from Medina had a clinical stroke, with eight having an abnormal CT scan [ 52 ]. When adults are included, the prevalences of stroke in the Western, SouthWestern (7.5%) and Eastern (6%) provinces of Saudi Arabia are high [ 53 , 54 , 55 , 56 ].…”
Section: Strokementioning
confidence: 99%
“…From a hospital-based study of SCD in the western part of Saudi Arabia, the incidence of overt stroke in children was reported to be 9.4% in a predominantly African (severe) haplotype [ 7 - 9 ]. While in Eastern Province this statistic is around 6% [ 10 ]. It is expected to be lower considering its less severe phenotype due to the high hemoglobin F percentage (Arab-Indian haplotype) compared to the severe African type seen in the Southwestern region, which all of our patient cohort represents [ 7 ].…”
Section: Introductionmentioning
confidence: 99%